Analisis Faktor Implementasi E-Government Di Kabupaten Jayawijaya Papua - Syarifah, Syarifah; Muksin, Dafrin; Fadlan, Muhammad (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2023)
The development of e-government innovation in Indonesia in recent years has been initiated to create an integrated government system at both central and regional government levels. E-government has a very good impact on the implementation of government, namely the implementation of effective and efficient government. The aim of this research is to examine and analyze the factors that influence the implementation of e-government in the 3T Region of Jayawijaya Regency, Papua. This research using descriptive and qualitative methods. The sample in this study was 10 ASN in the Jayawijaya OPD and 100 Jayawijaya Regency residents. The indicators used are ease of access, always available, security and trust, integration, and cost. Based on data analysis, the results show that the indicators for ease of access, always available, security and trust, and integration received a poor rating. Then the implementation of e-government on cost indicators is felt to be cost-effective by the people of Jayawijaya Regency. Apart from that, it was found that there were 4 supporting factors and 6 inhibiting factors in implementing e-government. In this way, it is hoped that this research can be used as evaluation material in the implementation of e-government in the 3T Region of Jayawijaya Regency.